Keberkesanan perkhidmatan bas mini di Kota Kinabalu Sabah (The effectiveness of the mini bus services in Kota Kinabalu, Sabah) - Harifah Mohd Noor; Mazdi Marzuki; Jabil Mapjabil; Oliver Valentine Eboy (Geografia, 2016)
Minibus is an alternative mode of public transport in Kota Kinabalu, Sabah. Nevertheless, its function is frequently associated with ineffectiveness services. This paper identifies components of an effectiveness of the minibus services based on the findings of a survey involving 988 respondents in Kota Kinabalu. Factor analysis and Confirmatory Factor Analysis (CFA) is used to analyse a total of 24 parameters effectiveness of the minibus. This study succeeded in developing three dimensions of the minibus service attributes effectiveness, namely comfort, accessibility, and safety. The mean score for its accessibility factor for minibus is higher compared to comfort and safety factor. These findings show that the minibus is needed in Sabah due to its accessibility. Consequently, comfort and safety factors minibus should be given priority by the agencies for improvement to attract more people to use public transport services.